2013
DOI: 10.1007/s00894-013-2029-z
|View full text |Cite
|
Sign up to set email alerts
|

A DFT study on the thermal cracking of JP-10

Abstract: Density functional theory (DFT) calculations have been carried out to investigate the thermal cracking pathways of JP-10, a high energy density hydrocarbon fuel. Thermal cracking mechanisms are proposed, as supported by our previous experimental results (Xing et al. in Ind Eng Chem Res 47:10034-10040, 2008). Using DFT calculations, the potential energy profiles of the possible thermal cracking pathways for all of the diradicals obtained from homolytic C-C bond cleavage of JP-10 were derived and are presented h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…6b is C1-C2 → C7-C10 → C8-C9 and the H attached to C6 shifts to C2 before the cleavage of C7-C10 bond. These reaction steps are also found in DFT calculations [20]. discovered in many studies [6,7,12,14,17].…”
Section: Effects Of Fgs Addition On Jp-10 Oxidationsupporting
confidence: 67%
See 2 more Smart Citations
“…6b is C1-C2 → C7-C10 → C8-C9 and the H attached to C6 shifts to C2 before the cleavage of C7-C10 bond. These reaction steps are also found in DFT calculations [20]. discovered in many studies [6,7,12,14,17].…”
Section: Effects Of Fgs Addition On Jp-10 Oxidationsupporting
confidence: 67%
“…The initial step of decomposition for every single JP-10 molecule in the systems of JP-10 pyrolysis and its mixture with FGS is presented in Table 1 and the corresponding time of occurrence is given. The JP-10 pyrolysis has been well studied by both experiment [12][13][14] and numerical modelling [17,19,20,46] before, so this section focuses on the analysis of effects of FGS addition on the JP-10 pyrolysis. In consistency with Ashraf and van Duin's [39] and the initiation of these 4 JP-10 molecules all occurs earlier than the first JP-10 decomposition without FGS.…”
Section: Effects Of Fgs Addition On Jp-10 Pyrolysismentioning
confidence: 99%
See 1 more Smart Citation
“…Chenoweth et al [13] used a reactive force field (ReaxFF) to identify major initial decomposition pathways including (a) a path leading to the formation of ethene and a C8 hydrocarbon and (b) a path producing two C5 hydrocarbons. Various reactions paths have also been studied by Yue et al [14] using the M06-2X functional. Recent work by Magoon et al [15] focused on calculating energy barriers for intramolecular disproportionation reactions that are important during the pyrolysis of JP-10.…”
Section: Introductionmentioning
confidence: 97%
“…The single-component hydrocarbon fuel Jet Propellant-10 (JP-10) is used in detonation engines, missiles, and supersonic combustion ramjets, where a fuel is required to have high thermal stability, high-energy density, and low freezing point. Because of its broad applications, the principal constituent of JP-10, tricyclo­[5.2.1.0 , ]­decane ( exo -tetrahydrodicyclopentadiene; exo -TCD; C 10 H 16 ; Figure ), has attracted significant attention of researchers, and numerous experimental, theoretical, and modeling studies of its pyrolysis and combustion have been reported in the literature. A detailed overview on the JP-10 studies was provided in our recent publication, and here we only briefly reiterate its key points.…”
Section: Introductionmentioning
confidence: 99%